Self-Inflated Barrier for Flood Protection with Water Level Monitoring by Internet of Things (IoT) - Asfaazam, Eekroq (Universiti Teknologi PETRONAS, 2020)
This work comprises a study of self-inflated barrier for temporary flood protection with monitoring system. This study started off with a system using tire as the selfinflated item. The monitoring system is using internet of things (IOT) method. Microcontroller that control the system is NodeMCU ESP8266 as the wireless device. This works covers how to build the temporary barrier and how it work to stop flood from flowing protected area. Water level sensor is included to show water increase and decrease. This water level data is shown in a phone application where we can open easily and monitor anywhere and anytime. This system can be used and tested in a flood area like in the east coast where monsoon hit and cause heavy flood almost every year, since Malaysia is greatly influenced by topography and monsoon winds.